Descriptions of Neboissomina, new genus and 6 new species of Ecnomidae from Australia (Trichoptera) - Cartwright, David I. (Zootaxa, 2011)
Descriptions and keys are provided for males of 7 ecnomid caddisfly species, with 6 species new to science and to Australia. Females of 5 species are also described. These species are placed in the new genus, Neboissomina, new genus. The following new species are described: N. jardinei, N. kuranya, N. mida, N. persona, N. philsuteri, and N. riyala. A new combination is suggested for N. krokale (Neboiss, 1979). The new genus is erected based on unique characters in the male and female genitalia, wings and setal warts of the head. Neboissomina, new genus is endemic to northern and eastern Australia.